STRENGTHENING INDIVIDUAL TAXPAYER COMPLIANCE THROUGH UNIVERSITY TAX CENTERS: EVIDENCE FROM THE IMPLEMENTATION OF INDONESIA'S HARMONIZATION OF TAX REGULATIONS - Wimba Respatia (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2026)
This study investigates the strategic role of the STIESIA Tax Center in enhancing individual taxpayer compliance during the implementation of Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (UU HPP), with particular emphasis on the Voluntary Disclosure Program (PPS). The study adopts a qualitative case study approach to explore how university-based Tax Centers contribute to strengthening taxpayers' understanding and compliance with newly introduced tax regulations. Data were collected through semi-structured interviews with four purposively selected informants, comprising individual taxpayers, a Tax Center user, and a tax consultant. The interview data were complemented by participant observation and documentary analysis. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while methodological triangulation was employed to enhance the credibility and trustworthiness of the findings. The results reveal that the STIESIA Tax Center performs three strategic functions in supporting taxpayer compliance. First, it serves as a tax education institution by disseminating information regarding the Harmonization of Tax Regulations and improving taxpayers' tax literacy. Second, it provides consultation and annual tax return assistance that reduce administrative uncertainty and increase taxpayers' confidence in fulfilling their tax obligations. Third, it functions as an intermediary institution that strengthens collaboration between taxpayers and the Directorate General of Taxes during the implementation of the Voluntary Disclosure Program. These findings suggest that voluntary taxpayer compliance is influenced not only by regulatory enforcement but also by educational support, institutional trust, and accessible consultation services. This study contributes to the literature by highlighting the institutional role of university-based Tax Centers in supporting tax reform and promoting voluntary taxpayer compliance in Indonesia.